2016
DOI: 10.14202/vetworld.2016.186-191
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and risks of zoonotic diseases among livestock farmers in Punjab

Abstract: Aim: The present study was conducted to assess the awareness, knowledge, and risks of zoonotic diseases among livestock farmers in Punjab.Materials and Methods: 250 livestock farmers were selected randomly and interviewed with a pretested questionnaire, which contained both open and close ended questions on different aspects of zoonotic diseases, i.e., awareness, knowledge, risks, etc. Knowledge scorecard was developed, and each correct answer was awarded one mark, and each incorrect answer was given zero mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 15 publications
8
33
3
Order By: Relevance
“…Literature that describes the level of rabies knowledge and associated attitudes and practices of people in India from backgrounds similar to those in the current study is limited. In a study of farmers who regularly attended GADVASU, Punjab, a greater proportion of participants (83%) than that observed in the current study were not only aware of rabies but also its zoonotic potential (Hundal, Sodhi, Gupta, Singh, & Chahal, ). This could in part be explained by these farmers’ overall higher socio‐economic status—they had all received formal education and not all were smallholders—which might increase their ability to seek, access and understand information about zoonotic diseases.…”
Section: Discussioncontrasting
confidence: 58%
“…Literature that describes the level of rabies knowledge and associated attitudes and practices of people in India from backgrounds similar to those in the current study is limited. In a study of farmers who regularly attended GADVASU, Punjab, a greater proportion of participants (83%) than that observed in the current study were not only aware of rabies but also its zoonotic potential (Hundal, Sodhi, Gupta, Singh, & Chahal, ). This could in part be explained by these farmers’ overall higher socio‐economic status—they had all received formal education and not all were smallholders—which might increase their ability to seek, access and understand information about zoonotic diseases.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, even though 63.5% respondents were aware of diseases that are transmitted through the consumption of raw cow milk, 50.9% of the respondents' forms of milk preference were raw milk. Hundal et al (2016) from Punjab were reported that 69.6% of the respondents drink raw milk and 55.6% of the respondents knew diseases can be transmitted through consumption of contaminated milk. Large amounts of E. coli, S. aureus, Candida albicans and other health hazard microbes have been reported in raw milk, cultured pasteurized milk and naturally soured raw milk (Gran et al, 2003), and this emphasizes need for improved hygienic practices and precaution at all levels of milk processing value chain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hundal et al. () of 250 livestock farmers in the Punjab showed that rabies awareness is high in this stakeholder group—most farmers were aware that rabies can be transmitted via a dog‐bite (98.4%) and that PEP can prevent rabies in humans (96.8%). Reports of dog‐bites (data received from the Directorate of Health and family Welfare, Punjab, unpublished results) demonstrated increased incidence in humans in the Punjab between 2010 and 2014 (Pearson's r = .92, 95% confidence interval 0.23‐1.00) despite a stable number of confirmed cases in dogs identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports that describe aspects of rabies control in India—for example, methods to improve coverage of dog vaccination and assessment of levels of rabies awareness (Gibson et al., ; Hundal, Sodhi, Gupta, Singh, & Chahal, ). However, we were unable to find recent descriptions of the reported distribution and occurrence of rabies cases in animals for the purpose of informing control strategies.…”
Section: Introductionmentioning
confidence: 99%